Movement Disability: Situations and Factors Influencing Access to Health Services in the Northeast of Thailand - Wongkongdech, A; Laohasiriwong, W (Kathmandu University Medical Journal, 2015)
Background Persons with movement disability (PWMDs) are the biggest group of persons with disabilities (PWDs) with needs helps especially on health. There has been no evident to show health services accessibility situation of PWMDs in the Northeast of Thailand, the biggest region. Objective This study aimed to explore the current situation of accessibility to health services among PWMDs, and factors influencing such access. Method This cross-sectional study used a multistage stratified random sampling to select 462 subjects from the national registered PWMDs poll to response to a structured questionnaire. This study complies with the principles of the Declaration of Helsinki and was approved by the Khon Kaen University Ethics Committee for Human Research prior to the data collection. Result We found that most of PWMDs (66%) had overall health service accessibility at medium level. Factors influencing the access to health services were living in rural area (adj. mean diff.= -24.01; 95 % CI: -45.88 to-2.31; p-value=0.032), high income (adj. mean diff.=0.002; 95 % CI: 0.001 to 0.005; p-value = 0.044), and having offspring or spouse as care givers (adj. mean diff.=40.44; 95% CI: 7.69 to 73.19; p-value=0.044; and adj. mean diff.=48.99; 95%CI: 15.01-82.98; p-value=0.016, respectively). PWMDs who lived in rural areas had better access to health services especially to the sub-district health promoting hospital than those in the urban area. Conclusion Accessibly to health services of PWMDs still limited. Income, care givers and residential areas had influences on their access. Kathmandu University Medical Journal Vol.12(3) 2014; 168-174